Pocket similarity identifies selective estrogen receptor modulators as microtubule modulators at the taxane site - Yu-Chen Lo (Nature Portfolio, 2019)
Taxanes are natural products which bind beta-tubulin, stabilize microtubules and have a broad spectrum of anticancer activity. Here authors employ a computational binding site similarity screen and cell-based assays to reveal a SERM cross-reactivity between the estrogen receptor and the beta-tubulin taxane binding pocket.